2022-LBA-1708-ESGO Will centralization of ovarian cancer treatment be beneficial in Poland ?. (27th October 2022) - Sznurkowski, Jacek Jan; Zawrocki, Anton; Kryniewska, Katarzyna
Abstract : Introduction: Background: Ovarian cancer mortality in Poland is over 15% higher than the average for the European Union. A postulated way to improve prognosis for polish ovarian cancer patients is the centralization of treatment in existing certified high-volume centers. However, Danish experience has shown that such organizational changes do not affect the survival. On the other hand, American studies suggest a huge benefit from centralization of treatment. Aim: To compare overall survival of advanced ovarian cancer patients treated in high and low volume centers in voivodeship with mean national mortality rate Methods: Data on reimbursement of treatment modalities of advanced ovarian cancer patients treated consecutively between 2012 -2019 in the Pomeranian Voivodeship were retrieved from the database of the National Health Fund and data on overall survival (OS) from the Polish National Cancer Registry. OS curves were estimated by the Kaplan-Meier method. P-values of <0.05 were significant. Results: 693 of 2015 identified C56 cases, were excluded due to reimbursement of surgical treatment only (suggesting early cancer stage or borderline). From remained 1322 cases, 57 were excluded due to unappropriated chemotherapy, leaving finally the group of similarly treated 1265 advanced C56 patients.Treatment of 1265 advanced C56 patients (surgery + chemotherapy +/- Bev) was conducted in 21 centers. Two of them were high-volume (ESGO certified: UCK & GCO with mean number of 52 cases annually) and 19 were low-volume (with mean number of 2 cases annually). 953/1265 (75.34%) and 312/1265 (24.66%) patients were treated in high and low-volume centers respectively. Conclusions: Centralization of treatment in existing certified high-volume centers will not improve prognosis of advanced C56 patients. Treatment volume of the center seems to be unapropriate measure of the quality of treatment in Poland.